2014
DOI: 10.1126/scitranslmed.3007523
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy Prolongs Survival and Restores Function in Murine and Canine Models of Myotubular Myopathy

Abstract: Loss-of-function mutations in the myotubularin gene (MTM1) cause X-linked myotubular myopathy (XLMTM), a fatal, congenital pediatric disease that affects the entire skeletal musculature. Systemic administration of a single dose of a recombinant serotype-8 adeno-associated virus (AAV8) vector expressing murine myotubularin to Mtm1-deficient knockout mice at the onset or at late stages of the disease resulted in robust improvement in motor activity and contractile force, corrected muscle pathology and prolonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
167
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 149 publications
(177 citation statements)
references
References 44 publications
5
167
2
3
Order By: Relevance
“…131 Since then, several groups have tested AAV-8 in normal 132 and affected dogs. 100,133,134 In contrast to the initial report by Ohshima et al, these later studies did not detect cellular immune reaction. Koo et al expressed a canine-microdystrophin in a 9-week-old affected dog without immune suppression.…”
Section: Cellular Immune Response To Aav-mediated Gene Transfer In Thcontrasting
confidence: 54%
“…131 Since then, several groups have tested AAV-8 in normal 132 and affected dogs. 100,133,134 In contrast to the initial report by Ohshima et al, these later studies did not detect cellular immune reaction. Koo et al expressed a canine-microdystrophin in a 9-week-old affected dog without immune suppression.…”
Section: Cellular Immune Response To Aav-mediated Gene Transfer In Thcontrasting
confidence: 54%
“…By far the most promising is related to myotubular myopathy. An international collaborative group demonstrated that gene therapy with MTM1 not only prevents, but also reverses, the phenotype of Mtm1 knockout mice [64]. This same group also demonstrated the efficacy of local adenoassociated virus-Mtm1 infusion as a treatment for dogs with Mtm1 mutations.…”
Section: How Is the Disorder Treated?mentioning
confidence: 91%
“…9 A missense mutation in the MTM gene (c.465C > A; p.N155K) was discovered and a breeding colony subsequently was established. 9,11 Recently, we reported response to gene therapy in canine and rodent models of XLMTM 12 ; however, in this report a clinical evaluation strategy was not in place to assess dogs. A reliable method to monitor clinical response to therapy would strengthen further evaluation of this disease model.…”
Section: Introductionmentioning
confidence: 86%
“…For example, we recently reported that gene therapy markedly improved muscle weakness and respiratory impairment and prolonged life span to more than 1 year in treated XLMTM dogs. 12 Further analysis would be required to evaluate the utility of the described neurological severity scoring system in predicting response to treatment in this spontaneous animal model of XLMTM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation